KELAKAR BETHOOK IN PALEMBANG MALAY LANGUAGE: A LINGUISTIC ANALYSIS - Afriani, Susi Herti (Journal of Malay Islamic Studies, 2019)
This paper examines distinctive culturally-linguistic humour and directives in Palembang Malay language (hereafter referred as Palembangnese) in Indonesia. Two transcribed samples of Kelakar Bethook (KB) in Palembangnese humour were selected. The data analyses and discussion show the uniqueness of humour and directives in KB in Palembangnese. This present research contributes to the nature of linguistics in language documentation and extends the scope of speech act research in a non-western language. This study also contributes to enhancing the linguistic-cultural theory in Eastern language and culture. This research thereby contributes to distinguishing one facet of language Malay civilization by exploring distinctive cultural-linguistic practices and promoting a wider awareness of Palembangnese culture and humour.